A multicenter, cross-sectional, observational study of budesonide/formoterol maintenance and reliever therapy in real-world settings. (June 2017) - Lin, Jiangtao; Li, Jing; Yu, Wencheng; Liu, Yuejian; Liu, Chuntao; Chen, Ping; He, Huijie; He, Bei; Liu, Shuang; Zhou, Xiangdong
Abstract: Background: To assess the level of asthma control achieved with budesonide/formoterol in Chinese patients with asthma, based on the Global Initiative for Asthma (GINA) definition and Asthma Control Test (ACT) score. Methods: This multicenter, cross-sectional study (NCT01785901) evaluated asthma control levels in Chinese patients receiving physician-prescribed budesonide/formoterol treatment. Adults with a diagnosis of asthma ≥6 months and receiving budesonide/formoterol treatment ≥3 months before screening were consecutively enrolled. Data including medical and medication history were collected using face-to-face questionnaires and physical examinations during a single visit. Results: A total of 1483 asthma out-patients from 27 medical centers were enrolled; 217 (14.6%) were treated with budesonide/formoterol using a fixed-dose strategy and 1266 (85.4%) with the SMART (Symbicort ® Maintenance And Reliever Therapy) strategy. According to GINA criteria, asthma was controlled in 58.6% (95% CI: 56.1%–61.1%) of patients and was either controlled or partly controlled in 94.1% (95% CI: 92.8%–95.3%) of patients. According to ACT score, asthma was completely controlled in 22.4% (95% CI: 20.3%–24.6%) of patients and was either completely or well controlled in 83.3% (95% CI: 81.4%–85.2%) of patients. Multivariate logistic regression analysis revealed that a >5-year history of asthma and an age of >50 years were factors associated with lower levels of asthma control. Conclusions: This study demonstrated high levels of asthma control (GINA: controlled and partly controlled and ACT: completely and well controlled) in Chinese patients with asthma treated with budesonide/formoterol. Greater age and a longer disease history were associated with lower levels of asthma control. Trial registration: ClinicalTrials.govNCT01785901. Registered February 5, 2013. Highlights: Asthma control level with budesonide/formoterol in real-world in China was assessed. 1483 asthma out-patients from 27 medical centers were enrolled in this study. Asthma was controlled in 58.6% patients and partly controlled in 35.5% patients. Long asthma duration and old age were associated with lower control levels.